الاجتهاد المقاصدي في تفسير وتطبيق النصوص القانونية: مفهومه، مجالاته، مستلزماته مع استصحاب تجربة القضاء السوداني - الشريف، محمد المدني صالح (جامعة زيان عاشور الجلفة, 2020)
Adopting the locutionary interpretation of the legal text may, in some exceptional cases, contradict the intention of the legislator or the intention of the parties involved in contractual transactions. It is cases such as these that bring to light the importance of discretionary interpretation, which goes hand in hand with the intentions and the major and minor objectives of legislation. Similar to locutionary interpretation, which is based on the lexical meaning and the grammatical structure of the legal text as a way of interpreting the text, discretionary interpretation is guided by principles and constraints. The study is divided into three four sections. Section one includes an introduction to discretionary interpretation. Section two is dedicated to the circumstances in which discretionary interpretation is needed. Section three is a discussion of the requirements that must be met before discretionary interpretation can be used. Section four is a discussion of the connection between discretionary interpretation and the principle of legal safety, since discretionary interpretation might be avoided on grounds of fear of abuse and control.
في بعض الحالات الاستثنائية، قد يفضي تطبيق النص القانوني على حسب ما يفيده ظاهره إلى ما يناقض قصد المشرع من التشريع في أحقاق الحقوق ورد المظالم إلى أهلها، أو إلى ما يتناقض مع قصد أطراف العلاقة في المعاملات التعاقدية بين الأفراد، وفي هذه الحالة تظهر أهمية الاجتهاد المقاصدي الذي يستصحب المقاصد والغايات والأهداف الكلية والجزئية في تطبيق القواعد القانونية في الواقع العملي، وإذا كان الاجتهادي العادي في فهم وتطبيق النصوص القانونية استنادا إلى ظاهر منطوقها مضبوطا بقواعد اللغة المتعارف عليها حتى لا تخرج المحكمة على إرادة المشرع من التشريع، فإن للاجتهاد المقاصدي، أصوله التي يقوم عليها، وضوابطه التي تحكمه، لذلك قمست هذا البحث إلى ثلاثة مباحث، خصصت المبحث الأول للتعريف بالاجتهاد المقاصدي، وبيان أهميته، ثم خصصت المبحث الثاني لمجالات الاجتهاد المقاصدي، وهي الأحكام المبنة على العرف، وكيفيات المعاملات، والنوازل المستجدة، ثم خصصت المبحث الثالث، لما يستلزمه الاجتهاد المقاصدي من معرفة عامة بالقانون وأهدافه ومقاصده، وإلمام باللغة وطرق الاستنباط، ومعرفة بما يتطلبه فقه الواقع، أخيرا خصصت مطلب للحديث عن الاجتهاد المقاصدي ومبدأ الأمن القانوني، لكون هذا الاجتهاد قد يؤدي إلى تخوفات بخصوص استغلاله والجنوح نحو الهوي والتحكم.
Keywords: الاجتهادات المقاصدية -- النصوص القانونية -- القضاء السوداني -- الاختصاصات القضائية